Efeitos antinociceptivo, anti-inflamatório e antioxidante da entrecasca da Maytenus rigida Mart. (Celastraceae) - Conceição, Alexsandro Machado (2010)
Maytenus rigida Mart., populary known as bom-nome , cabelo de negro , casca grossa , and pau de colher is a species of Celastracae family that is widely distributed in the northeast. In folk medicine, it is indicated for the treatment of inflammation, pain, and infections such as in the urinary tract. This study aimed to contribute to the knowledge of the antinociceptive, anti-inflammatory, and antioxidant actions from the bark of M. rigida. To this end, the animals were pretreated orally with the crude ethanol extract (EE) of the inner bark of this plant at the doses of 100, 200, and 400 mg / kg and used in experimental models of nociception (writhing induced by acetic acid, hot plate and formalin in mice), inflammation (paw edema and carrageenan-induced peritonitis in rats) and oxidation (method of the scavenging of DPPH radical). In the writhing model, oral administration of the EE showed inhibitory activity on the writhing induced by acetic acid at the doses of 200 and 400 mg / kg (P <0.01). Pretreatment of animals with EE increased the latency time on hot plate at the doses of 200 and 400 mg / kg (P <0.05), suggesting a central action. In the formalin model, the EE had inhibitory activity in both test phases: the first phase at the doses of 200 and 400 mg / kg (P <0.01) and the second phase at the doses of 100, 200, and 400 mg / kg (P <0.05). Using the model of paw edema induced by carrageenan to evaluate a possible anti-inflammatory activity, we observed that oral administration of the EE was not able to inhibit the formation of edema in rats. However, pretreatment EE was effective in reducing the migration of leukocytes into the peritoneal cavity of rats at all doses used (P <0.01). Our results suggest that the EE of M. rigida inner possesses antinociceptive, anti-inflamatory and antioxidant activities.